Teaching Diversity, Becoming Inclusive: Perspectives and Possibilities in ASEAN Library and Information Science Schools. Issue 2 (3rd April 2018) - Maestro, Roselle S.; Ramos-Eclevia, Marian; Eclevia, Carlos L.; Fredeluces, John Christopherson L.T.
Abstract: This paper investigates how courses and topics about diversity and inclusion are being integrated into the Library and Information Science (LIS) curriculum among selected library schools in the member countries of the Association of Southeast Asian Nations (ASEAN). It also examines the characteristics and roles of culturally responsive LIS faculty in teaching cultural diversity-related issues. In addition, it discusses the approaches, challenges and barriers in advancing cultural competencies of LIS graduates. This study used a mix of qualitative survey research and content analysis of LIS course offerings. Findings show that ASEAN LIS education is inadequate in terms of integration of diversity and inclusion in core courses. Teaching cultural competence and diversity is a lifelong learning process of understanding and appreciating cultural similarities and differences. LIS students may develop their cultural competence through personal experience by engaging in library internship with all library types, community immersion and collaborative group work with diverse members. Infusing diversity-related issues and the principle of inclusion into the LIS curriculum is not easy, yet important and necessary.